Performance analysis of interface bonding and channel bonding at point to point wireless 802.11n - Shidik, Guruh Fajar (2011)
Point to Point (PtP) wireless connection allow separate place that used infrastructure mode and configured as wireless bridge to be interconnected. The implementation of this configuration is suitable for many conditions such as for connecting separate places on rural area and for non commercial like in military utilizing. Nowadays with the ever growing demand for high throughput bandwidth, Point to Point wireless connection should be able to serve more bandwidth for many kind applications such as real-time multimedia services. Requirement of throughput improvement on network connection, lead some techniques to achieve more bandwidth. Interface Bonding that already implement on wire Ethernet and Channel Bonding are two techniques that expected capable to improve throughput. The problems regarding Interface Bonding and Channel Bonding techniques at Point to Point wireless 802.11n connection are there has been no specific research that analyse the performance of Interface Bonding at Point to Point wireless 802.11n connection, furthermore comprehensive information about comparative analysis performance between Interface Bonding and Channel Bonding on Point to Point wireless 802.11n also has not been investigated. Moreover, Administrator network needs to know clearly, which techniques are capable to improve the performance of point to point wireless 802.11n connection at difference signal strength, directional flow or with different number of packet size. The Aims of this study are to analyse the performance of Interface Bonding and Channel Bonding when applied at Point to Point wireless 802.11n, where to measures the performance in this research, several parameters such as delay, jitter, data rate loss and throughput applied on TCP/UDP protocols. Afterwards, variables such as Packet Sizes, Signal Strength and Directional Traffic Flows would be uses to manipulate for testing both techniques. The research study was conducted at Lab environment that might be still has interference with other wireless devices, since the researcher cannot control the interference. The results showed that Channel Bonding has significant throughput improvement when applied at Point to Point connection used wireless 802.11n. This due to the capability of the Channel Bonding to optimize the available bandwidth of wireless 802.11n, by wider the bandwidth spectrum. However, a different result is obtained for the Interface Bonding, which is far from expectation. This is caused by Media Independent Interface (MII), and Scheduling Algorithm are unable to work properly at wireless 802.11n that is used in Point to Point connection. Hence, the performance of this Interface Bonding is lower than the single link. Therefore, it can be said that this technique is unable to improve the throughput.